2020
DOI: 10.1111/bjh.16448
|View full text |Cite
|
Sign up to set email alerts
|

Second‐line treatment trends and long‐term outcomes of 392 children with chronic immune thrombocytopenic purpura: the French experience over the past 25 years

Abstract: Summary Childhood chronic immune thrombocytopenic purpura (cITP) is a rare disease. In severe cases, there is no evidence for the optimal therapeutic strategy. Our aim was to describe the real‐life management of non‐selected children with cITP at diagnosis. Since 2004, patients less than 18 years old with cITP have been enrolled in the national prospective cohort, OBS’CEREVANCE. From 1990 to 2014, in 29 centres, 392 children were diagnosed with cITP. With a median follow‐up of six years (2·0–25), 45% did not n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 54 publications
0
29
0
Order By: Relevance
“…The higher rate of sustained CR in ITP among patients with pES compared to patients with cITP alone may be due to more patients with pES receiving treatment. 18 …”
Section: Discussionmentioning
confidence: 99%
“…The higher rate of sustained CR in ITP among patients with pES compared to patients with cITP alone may be due to more patients with pES receiving treatment. 18 …”
Section: Discussionmentioning
confidence: 99%
“…It could reverse T cell abnormalities in patients who have responded to therapy. [ 13 ] Previous studies showed that clinical symptoms in patients with chronic immune thrombocytopenia might not relieve by using EPAG alone. [ 14 ] Rituximab was used in a number of clinical treatments, including hematological malignancies, autoimmune diseases, and organ transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Since 2004, French patients with cITP diagnosed before 18 years of age have been included in the prospective OBS'CEREVANCE cohort. 9,17 The inclusion and exclusion criteria for the cohort are presented in Table S1. Written informed consent was obtained from all participants.…”
Section: Obs'cerevance Cohortmentioning
confidence: 99%
“…6 Pediatric cITP is associated with poor health-related quality of life, 7,8 and second-line treatments (i.e., other than corticosteroids and intravenous immunoglobulins) are required in up to 55% of patients. 9 Disease remission is common and almost 75% of cITP patients with pediatric-onset seem to undergo spontaneous remission during 5 years of follow-up. 6,10,11 Some patients with cITP have associated immunopathological manifestations (IMs), clinical IMs (such as lymphoproliferative disorder and organ autoimmunity), and/or biological IMs (such as antinuclear antibodies [ANA] and hypogammaglobulinemia).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation